Coalition Rule by Pakatan Harapan, 2018- 2020: Key Consociational Lessons - Muhammad Azzubair Awwam, Mustafa; Kartini, Aboo Talib Khalid; Nazri, Muslim (IIUM Press, 2025)
This article reassesses Pakatan Harapan’s (PH) 2018–2020 experience through Lijphart’s consociational framework. A qualitative approach is applied, triangulating semi-structured elite interviews with documentary sources and news reports. Findings show that PH built a broad grand coalition across ethnic and regional lines, applied corrective proportionality by granting Malay-based parties disproportionate cabinet weight to secure ethnic legitimacy, relied on improvised rather than institutionalised segmental autonomy and treated mutual veto as informal bargaining rather than a binding safeguard. These design choices produced short-term legitimacy but weak internal cohesion, leaving the coalition vulnerable to defections, culminating in the ‘Sheraton Move.’ The study provides an empirically grounded account of Malaysia’s post-BN hegemonic coalition governance and demonstrates how inclusion without enforceable rules limits the durability of consociational arrangements.